2021
DOI: 10.1111/os.13058
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anterior Cervical Discectomy and Fusion with Cervical Laminectomy and Fusion in the Treatment of 4‐Level Cervical Spondylotic Myelopathy

Abstract: Objective: To assess and compare the therapeutic effects of Anterior Cervical Discectomy and Fusion (ACDF) and Cervical Laminectomy and Fusion (CLF) in the treatment of 4-level cervical. Methods:We performed a retrospective review on 39 patients with 4-level CSM who underwent ACDF or CLF in the Third Hospital of Hebei Medical University from January 2010 to December 2018. The patients were divided into ACDF group and CLF group according to the treatment. The operative index was evaluated based on intraoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The risk of postoperative dysphagia, cage subsidence, and nonunion may be higher with multi-stage ACDF [ 4 , 5 , 7 ]. In our study, no cage subsidence was found in the anterior group, and according to Bridwell fusion grade [ 20 ], anterior fusion reached grade I in 28 cases (71.8%) and grade II in 10 cases (25.6%) in the anterior group, and posterior fusion reached grade I in 25 cases (75.8%) and grade II in 8 cases (24.2%) in the posterior group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk of postoperative dysphagia, cage subsidence, and nonunion may be higher with multi-stage ACDF [ 4 , 5 , 7 ]. In our study, no cage subsidence was found in the anterior group, and according to Bridwell fusion grade [ 20 ], anterior fusion reached grade I in 28 cases (71.8%) and grade II in 10 cases (25.6%) in the anterior group, and posterior fusion reached grade I in 25 cases (75.8%) and grade II in 8 cases (24.2%) in the posterior group.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical decompression can enhance neurological function and prevent future deterioration [ 1 , 2 , 3 ]. Although surgical treatments have greatly enhanced over the last few decades, there is still no consensus approach for treating multilevel DCM (MDCM), particularly 4-level DCM [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These treatments often provide a positive outcome for the patient and are associated with a low rate of complications. [9][10][11][12][13][14] The overall rate of any complication experienced a significant decline from 2006 to 2016 after the introduction of ACF (24.5 to 20.8 per 1000 inpatient days). 9 Some studies have shown that anterior cervical discectomy and fusion (ACDF) was associated with lower intraoperative blood loss and better cervical lordosis preservation.…”
Section: Introductionmentioning
confidence: 99%
“…9 Some studies have shown that anterior cervical discectomy and fusion (ACDF) was associated with lower intraoperative blood loss and better cervical lordosis preservation. 10,11 Anterior cervical corpectomy with fusion (ACCF) is the preferred surgical procedure due to its higher improvement in Japanese Orthopaedic Association (JOA) score following treatment for the ossification of posterior longitudinal ligament (OPLL). 14 Significant intraoperative blood loss (SIBL), which was defined as intraoperative blood loss of 500 mL or more, may result in hypotension, hypoxia of tissues and organs, and nerve ischemic injury, thus increasing the recovery time and the morbidity and complication rates.…”
Section: Introductionmentioning
confidence: 99%